2014
DOI: 10.1186/1748-717x-9-149
|View full text |Cite
|
Sign up to set email alerts
|

Treatment fractionation for stereotactic radiotherapy of lung tumours: a modelling study of the influence of chronic and acute hypoxia on tumour control probability

Abstract: BackgroundStereotactic body radiotherapy (SBRT) for non-small-cell lung cancer (NSCLC) has led to promising local control and overall survival for fractionation schemes with increasingly high fractional doses. A point has however been reached where the number of fractions used might be too low to allow efficient local inter-fraction reoxygenation of the hypoxic cells residing in the tumour. It was therefore the purpose of this study to investigate the impact of hypoxia and extreme hypofractionation on the tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 35 publications
3
28
0
1
Order By: Relevance
“…Instead, multi-fraction brain SRT was predicted to produce slightly better TCPs than single-fraction treatments for brain metastases. These conclusions are consistent with expected effects on hypoxic tumors, where fractionation allows tumor reoxygenation between fractions [41][42][43].…”
Section: Discussionsupporting
confidence: 90%
“…Instead, multi-fraction brain SRT was predicted to produce slightly better TCPs than single-fraction treatments for brain metastases. These conclusions are consistent with expected effects on hypoxic tumors, where fractionation allows tumor reoxygenation between fractions [41][42][43].…”
Section: Discussionsupporting
confidence: 90%
“…LOCs were assumed to take place, meaning that the oxygen tension was assumed to change at the cellular level as a result of changes in acute hypoxia. This was achieved by randomly shutting down a fraction of vessels at each treatment fraction, while the average intervessel distance within each tumor region remained the same throughout the full course of treatment, leading to a redistribution of the p O 2 values between voxels at each fraction [12, 17, 19, 20]. The overall geometry of the tumor with its hypoxic island, and the corresponding hypoxic fractions of the different regions, therefore, remained the same for all fractions (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…However, another type of reoxygenation, resulting from changes in acute hypoxia between fractions, should also be considered [911]. In a recent study by Lindblom [12], the influence of such local oxygenation changes (LOCs) on the outcome of stereotactic body radiotherapy (SBRT) using photons was investigated. The study showed that extreme hypofractionation (using one single fraction) should be pursued with caution, since it might result in reduced local control as a result of the reduced possibilities of interfraction LOCs.…”
Section: Introductionmentioning
confidence: 99%
“…For example, there is evidence that single-fraction stereotactic RT lacks a dose-response relationship and achieves lower tumor control rates than 3 or more fractions even if the same ‘biologically effective doses' are applied [105,106], which is consistent with a detrimental effect of missing re-oxygenation [107]. Oxygen is required for the production of superoxide from cell water radiolysis products, which greatly enhances the toxicity of IR [57].…”
Section: Combining Ketogenic Metabolic Therapy With Radiotherapy To Ementioning
confidence: 82%